2019
DOI: 10.1038/s41598-019-54865-w
|View full text |Cite
|
Sign up to set email alerts
|

Common genetic variants associated with Parkinson’s disease display widespread signature of epigenetic plasticity

Abstract: Parkinson disease (PD) is characterized by a pivotal progressive loss of substantia nigra dopaminergic neurons and aggregation of α-synuclein protein encoded by the SNCA gene. Genome-wide association studies identified almost 100 sequence variants linked to PD in SNCA. However, the consequences of this genetic variability are rather unclear. Herein, our analysis on selective single nucleotide polymorphisms (SNPs) which are highly associated with the PD susceptibility revealed that several SNP sites attribute t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…Similar observations have been reported previously 14,25,29 . However, the mechanism underlying this differential regulation remains unclear and is likely associated with the existence of 2 adjacent DNA methyltransferase 1 docking sites 30 …”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similar observations have been reported previously 14,25,29 . However, the mechanism underlying this differential regulation remains unclear and is likely associated with the existence of 2 adjacent DNA methyltransferase 1 docking sites 30 …”
Section: Discussionsupporting
confidence: 85%
“…14,25,29 However, the mechanism underlying this differential regulation remains unclear and is likely associated with the existence of 2 adjacent DNA methyltransferase 1 docking sites. 30 One concern is whether the status of DNA methylation in peripheral blood cells can serve as a biomarker for iRBD, in which cell damage primarily occurs in the brain. A few studies have already illustrated an association between peripheral DNA methylation and changes in the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Disruptive variants at these loci could be contributing to diseaseassociated changes in the deposition of these marks and, in extension, contribute to an intermediate disease phenotype. Such interplay was recently also shown at the SNCA locus, where a differentially methylated region in PD patients (Jowaed et al 2010) was also found to contain PD-associated variants and that this site is a target for DNA demethylases (Sharma et al 2019). These findings highlight the complex interconnection of regulatory marks and genetics and the inherent difficulty to dissociate environment-or diseaseassociated contributions from genetic effects on DNA and histone modifications.…”
Section: Epigenetic Changes In Neurodegenerative Diseasesmentioning
confidence: 64%
“…Despite a large number of studies that have addressed the local/global DNA methylation changes in multiple human cancers and other diseases [11,15,16], the key link showing the switch towards the dynamics of DNA hypo-/hypermethylation is still missing. Perhaps, defining the distinct roles of hypo-and hypermethylation within the same individual might help to undermine their potential consequences.…”
Section: Introductionmentioning
confidence: 99%